+0  
 
0
330
6
avatar

i want to help me if it posible

 Nov 5, 2017
 #1
avatar+637 
0

Is it possible to translate into Enlgish?

 Nov 5, 2017
 #2
avatar+99297 
+2

7.1

It is important to note that both the numerator and the denominator tend to 0 so I will use L'Hopital's rule.

 

 

\(\displaystyle\lim_{x\rightarrow 2}\;\frac{x^2-x-2}{x^2-3x+2}\\ =\displaystyle\lim_{x\rightarrow 2}\;\frac{\frac{d}{dx}(x^2-x-2)}{\frac{d}{dx}(x^2-3x+2)}\qquad \text{Using L'hopital's Rule }\\ =\displaystyle\lim_{x\rightarrow 2}\;\frac{2x-1}{2x-3}\\ =\frac{3}{1}\\ =3\)

.
 Nov 6, 2017
 #3
avatar+99297 
+2

Это лучший способ сделать это.

This is a better way to do it.

 

\(\displaystyle\lim_{x\rightarrow 2}\;\frac{x^2-x-2}{x^2-3x+2}\\ =\displaystyle\lim_{x\rightarrow 2}\;\frac{(x-2)(x+1)}{(x-2)(x-1)}\\ =\displaystyle\lim_{x\rightarrow 2}\;\frac{(x+1)}{(x-1)}\\ =\frac{3}{1}\\ =3\)

 

.
 Nov 6, 2017
edited by Melody  Nov 6, 2017
 #4
avatar+98125 
+2

5.1( a )   arcsin [ cos (pi/3) ] - sin [ arcsin (-1/2) ]  =

               arcsin [ 1/2]  -   (-1/2)

                  pi / 6  +  1/2

      

      (b)  arctan [cos (pi) ] -  arctan [ tan (3pi/ 7) ]  =

             arctan [ -1]    -     3pi/ 7

                - pi/ 4    -   3pi / 7

                 - [ 7 pi  + 12 pi ]  /28

                   - 19pi  / 28

 

5.2 ( a)  arccos [ cos (pi/5) ] - sin [ arctan (-1) ]  =

                   pi  / 5    -    sin [ - pi / 4 ]

                   pi  / 5   -   [ - 1 / √2] 

                   pi  / 5   +  [ 1 / √2]

                   

 

      (b )  arctan [ cos (pi/3) ] -  tan [ arctan (3pi / 7) ] =

              arctan [ 1/2 ]  -  3pi / 7 

 

5.3   (a)  arccos [ cos (pi / 5) ] - sin [ arctan (-1) ]  =

                pi  / 5    -  sin  [ - pi / 4 ] =

                pi  / 5  -  [ - 1 / √2 ]  =

                pi / 5   +  [1 / √2 ]

 

          (b) same as  5.2 (b)

 

 

cool cool cool

 Nov 6, 2017
 #5
avatar+98125 
+2

lim           √ [2 - x ] - 1

x →1        _________

                     x  - 1

 

 

lim           √ [2 - x ] - 1        √ [2 - x ] + 1 

x →1        _________        __________

                     x  - 1              √ [2 - x ] + 1 

 

lim                2  - x  - 1

x → 1          __________________

                   ( x - 1) (   √ [2 - x ] + 1)

 

lim

x → 1          1 - x

                   ___________________

                   ( x  - 1)  (   √ [2 - x ] + 1)

 

 

lim             - ( x  - 1 )

x → 1       ______________________

                    ( x - 1)  (   √ [2 - x ] + 1)

 

lim                 -1                                                     -1

x → 1          _________________      =              ____     

                     √ [2 - x ] + 1                                       2

 

https://www.desmos.com/calculator/ev6xzdsszs

 

 

cool cool cool

 Nov 6, 2017
 #6
avatar+98125 
+2

lim                sin (x)

x → pi          _____

                     x -  pi

 

Note   sin (pi- x)  =  sin pi cosx  - sinx cospi  =   sin (x)   .....so........

 

lim            sin ( pi - x)         

x → pi      ________     

                      x - pi           

 

 

 

 1           lim               sin ( pi - x)

__  *     x → pi        __________

-1                                ( pi - x )

 

 

 

 

Note       lim        sin (pi - x)                      lim          sin (x)

             x→ pi     _______       =           x → 0        _____        =    1

                               pi - x                                            x

 

So

 

 

lim                sin (x)

x → pi          _____        =   (-1) * (1)    =   -1

                     x -  pi

 

 

 

cool cool cool

 Nov 6, 2017

9 Online Users

avatar